Photoswitchable and thermosensitive fluorescent liposomes - Lim, Jin Heng (Nanyang Technological University, 2021)
Liposomes are versatile nanomaterials used in a variety of applications such as drug delivery and bioimaging. In this study, three asymmetrical squaraine dyes were synthesized and embedded in liposomes in the efforts to find a suitable dye that can be used for bioimaging procedures involving liposomes. The optical properties of the synthesized dyes as well as their liposomes were studied and compared to the previously synthesized asymmetrical squaraine dye SQR22 and its liposome form.